EFEK ANTIHIPERGLIKEMIK EKSTRAK ETANOL DAUN BENALU KERSEN (Dendrophthoe pentandra (L.) Miq) PADA TIKUS PUTIH JANTAN YANG DIINDUKSI ALOKSAN - Adiyatma Putra Mahardika; Sadakata Sinulingga; Medina Athiah; Subandrate Subandrate (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
This study aims to determine the effect of lowering blood glucose. The study was conducted in an experimental laboratory in vivo with one group randomized prepost-test design. The extract was made through the gradual maceration process of Benalu Kersen leaf simplicia with ethanol solvent. The extract was divided into three groups with doses of 65 mg / kg, 130 mg / kg, and 260 mg / kg of body weight. The sample used was 9 male white rats (Rattus norvegicus) which were randomly divided into three groups. Blood glucose levels were measured before induction, after induction, after 7 days, and after 14 days of giving the extract. Data analysis was performed in the form of homogeneity test, normality test, paired t-test using Excel and SPSS programs. There was significant decrease in blood glucose levels on day 0 to day 7 in dose II group. The largest percentage reduction in blood glucose levels was shown in dose II group, namely 32.6%, followed by dose I group at 18.89%. The ethanol extract of Benalu kersen leaves did have an effect of lowering blood glucose levels on alloxan-induced male white rats.